The Picture of Arabic Linguistics and the Priorities thereof in Arabic Linguistic Academies: Arabic Linguistic Academics of Damascus and Cairo: A Case Study - Abu Saleh, Khuloud; Elyaboudi , Khalid (Al-Adab Journal, 2024)
The science of linguistics emerged in the West reflecting the scientific methodology of studying linguistic phenomena cross-linguistically. This has earned linguistics a prominent position among modern sciences since the early twentieth century. This progress of linguistic study reached the Arab world, contributing to the inception of modern Arabic linguistics in the mid-20th century at the hands of those researchers who were keen on applying various linguistic theories to the study of the Arabic language. Among those pioneers were members of scientific institutions, such as Arabic linguistic academies, whose contributions were manifest in their works that articulate their research interests and future objectives for the advancement of Arabic linguistics. This research aims to uncover the linguistic influence exerted by the pioneers of Arab academies. It draws upon publications in the journals of linguistic academies and the proceedings of their conferences (with a special focus on the Arabic Language Academy in Damascus and the Arabic Language Academy in Cairo). Further, it seeks to analyze the contents of these publications within the broader scope of linguistic schools and modern trends. The findings of the study revealed the existence of a linguistic crisis within the Arabic language academies in Damascus and Cairo. Thus, the study encourages the establishment of priorities considering the contemporary Arabic language reality and the challenges it confronts in the modern epoch.